The Measurement of Permanent Income and Its Application to Savings Behavior - Bhalla, Surjit S. (Journal of Political Economy, 1980)
A unique feature of this study is its use of panel data to construct two measures of permanent income: An earnings function with unobserved individual differences suggests one measure, while a weighted average of past incomes yields another. These measures reject the accepted theories of savings behavior and suggest a nonlinear relationship between savings and permanent income. A new function incorporating this nonlinearity is successfully applied to the data for Indian farm households. The occurrence of this nonlinearity suggests that income redistribution policies in the less developed countries are likely to result in a reduced supply of household savings.